Integration of Dhikr and Sufistic Meditation in Islamic Religious Education: An Analysis of Al-Ghazali's Thought and Its Implications - Irfan Rizkiana Raja Nugraha; Agus Fakhruddin; Cucu Surahman (Fakultas Agama Islam Universitas Billfath, 2025)
This study aims to explore and formulate the concept of dhikr (remembrance of God) and Sufi meditation as part of the development of teaching methods in Islamic Religious Education (PAI), with a focus on improving moral character and enhancing students' mental well-being. The study employs a qualitative approach using a literature review method, following Cooper’s six steps: (1) defining the research problem, (2) collecting data, (3) evaluating data, (4) analyzing and organizing information, (5) interpreting findings, and (6) presenting results. The primary data source for this study is Ihya Ulumuddin by Al-Ghazali, complemented by secondary sources such as books and scholarly journal articles. The findings conclude that integrating dhikr and meditation into teaching methods not only facilitates the transformation of students’ moral character but also helps reduce stress, enhance psychological tranquility, and strengthen spiritual awareness. Theoretically, this research contributes to the academic discourse on integrating dhikr and meditation into Islamic education pedagogy. Practically, implementing this method can help students improve focus, alleviate stress, fill spiritual voids, and refine their moral character.